Prevalence of nosocomial infection and antibiotic use at a university medical center in Malaysia - Hughes, A.J.; Ariffin, N.; Huat, T.L.; Molok, H.A.; Hashim, S.; Sarijo, J.; Latif, N.H.A.; Abu Hanifah, Y.; Kamarulzaman, A. (2005)
Most reports of nosocomial infection (NI) prevalence have come from developed countries with established infection control programs. In developing countries, infection control is often not as well established due to lack of staff and resources. We examined the rate of NI in our institution. METHODS: A point-prevalence study. of NI and antibiotic prescribing was conducted. On July 16 and 17, 2001, all inpatients were surveyed for NI, risk factors, pathogens isolated, and antibiotics prescribed and their indication. NIs were diagnosed according to CDC criteria. Cost of antibiotic acquisition was calculated by treatment indication. SETTING: Tertiary-care referral center in Malaysia. PATIENTS: All inpatients during the time of the study. RESULTS: Five hundred thirty-eight patients were surveyed. Seventy-five had 103 NIs for a prevalence of 13.9. The most common NIs were urinary tract infections (12.2), pneumonia (21.4), laboratory-confirmed bloodstream infections (12.2), deep surgical wound infections (11.2), and clinical sepsis (22.4). Pseudomonas aeruginosa, MRSA, and MSSA were the most common pathogens. Two hundred thirty-seven patients were taking 347 courses of antibiotics, for an overall prevalence of antibiotic use of 44. NI treatment accounted for 36 of antibiotic courses prescribed but 47 of antibiotic cost. Cost of antibiotic acquisition for NI treatment was estimated to be approximately 2 million per year (Malaysian dollars). CONCLUSION: Whereas the rate of NI is relatively high at our center compared with rates from previous reports, antibiotic use is among the highest reported in any study of this kind. Further research into this high rate of antibiotic use is urgently required.